Method for preparing compound fertilizer by activating potassium fluosilicate slag
By activating the potassium fluorosilicate residue and combining bentonite modification and the use of amino acids, compound fertilizers were prepared, which solved the problem of unstable nutrient release rate of existing compound fertilizers, and achieved stable nutrient release and improved crop yield.
Patent Information
- Application Number
- CN202510199636.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-24
AI Technical Summary
The nutrient release rate of existing compound fertilizers is unstable and cannot meet the growth needs of crops, resulting in low crop yields and susceptible to pests and diseases.
Compound fertilizers are prepared by activating potassium fluorosilicate residues, and ammonia water is activated to generate ammonium fluoride and potassium fluoride. Combined with the modification of bentonite and the use of amino acids, a stable three-dimensional network structure and secondary coating layer are formed to achieve stable nutrient release.
The nutrient release rate is stable, meets the needs of crop growth, improves crop yield and pest resistance, and improves soil structure and fertility.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of compound fertilizers, and particularly relates to a method for preparing compound fertilizer by activating potassium fluorosilicate slag. Background Art
[0002] my country is a major agricultural country and also a major producer and user of fertilizers. Fertilizers are important agricultural inputs and have played a positive role in increasing agricultural production and income and ensuring food security. The use of fertilizers has greatly promoted the development of my country's agriculture. At present, my country's agricultural development has entered a new stage, adjusting from a high-input, high-consumption quantity-scale model to a green development model that emphasizes both quality and efficiency.
[0003] Compound fertilizer refers to a fertilizer containing at least two of the three main nutrient elements of nitrogen, phosphorus and potassium. It has a high nutrient content, few by-products, good physical properties, no adverse effects on the properties of the soil, is easy to store and transport, and is easy to apply mechanically. At present, compound fertilizer is an important type of fertilizer used in agricultural production in my country. It is used in a wide area and in large quantities, and is an important guarantee for the safety of agricultural products.
[0004] However, the extensive use of compound fertilizers has led to serious soil compaction and excessive pH values, which has greatly reduced the quality of crops and increased farmers' farming costs. In addition, serious diseases and insect pests have occurred in the later stages of crop growth, greatly affecting crop yields.
[0005] As a high-quality fertilizer, slow-release fertilizer has a higher fertilizer efficiency than conventional chemical fertilizers. It can reduce the loss of fertilizer nutrients in the soil, reduce environmental pollution and adverse effects on the soil, and reduce the number of fertilization operations, avoiding the adverse effects of excessive fertilization on crop seedlings, which is beneficial to promoting the quality of agricultural products and food safety.
[0006] Potassium fluorosilicate slag is a by-product of the phosphorus and potassium workshop, in which the potassium fluorosilicate content is about 50wt%, the water-soluble phosphorus is about 7.5wt%, and the water-soluble potassium is about 9.0wt%. It contains relatively high content of phosphorus and potassium elements, which can participate in the regulation of plant cell osmotic pressure, promote the transportation of photosynthesis products, promote the development of plant roots, and promote the healthy growth of crops; After searching, the applicant found that there is no mature process for using potassium fluorosilicate slag to prepare compound fertilizer; therefore, it is of great research significance to use potassium fluorosilicate slag to prepare compound fertilizer with slow-release properties.
[0007] During the research and development process, it was found that applying potassium fluorosilicate residue directly to the soil cannot meet the growth needs of crops, and its fertilizer efficiency is poor, the crops do not absorb and utilize nutrients effectively, and the effect of promoting crop yield and quality is not obvious; the applicant also found that the compound fertilizer with slow-release properties prepared by the prior art still has the problem of unstable nutrient release rate, which affects the normal growth performance and disease and pest resistance of crops, and ultimately leads to low crop yield. Summary of the invention
[0008] In order to solve the technical problems existing in the prior art, the present invention provides a method for preparing compound fertilizer by activating potassium fluorosilicate slag, which has a stable nutrient release rate, meets the growth needs of crops, effectively promotes the normal growth and disease and pest resistance of crops, and increases crop yields.
[0009] In view of the above technical problems, the present invention adopts the following technical solutions: A method for preparing compound fertilizer by activating potassium fluorosilicate slag, comprising activation, primary compounding and secondary compounding steps, and the specific operations are as follows: 1. Activation Potassium fluorosilicate is placed in deionized water, stirred evenly, and then an ammonia solution is added, and the temperature is raised to 60-90°C for stirring reaction, and the reaction time is 90-120 minutes. After the reaction is completed, the temperature is naturally lowered to room temperature, and the filtrate is obtained by suction filtration. The filtrate is concentrated to 28-33% of the original volume at 58-62°C, and dried at 50-54°C to obtain a primary compound fertilizer; The mass ratio of potassium fluorosilicate to deionized water is 10-50:50-90; The mass concentration of the ammonia solution is 15-25%; The molar ratio of potassium fluorosilicate to ammonia is 1:5-10.
[0010] 2. One-time compound (1) Primary modified bentonite The bentonite is placed in a pre-modified liquid for soaking at a temperature of 48-52°C for a soaking time of 32-38 minutes. After the soaking is completed, the amino acid mixture is added, and the mixture is stirred for 48-52 minutes, and then filtered, washed, and dried to obtain a primary modified bentonite. The particle size of the bentonite is 100-120nm; The mass ratio of the bentonite, the pre-modified liquid and the amino acid mixture is 9.3-9.8:95-110:3.2-3.7; The pre-modified liquid is prepared by uniformly mixing 37-42wt% ethanol solution, kH602, hexadecyltrimethylammonium bromide and sodium lignin sulfonate, wherein the mass ratio of the 37-42wt% ethanol solution, kH602, hexadecyltrimethylammonium bromide and sodium lignin sulfonate is 120:1.1-1.5:1.5-2.0:0.8-1.2; The preparation method of the amino acid mixture comprises the following steps: placing calcium carbonate in a potassium hydroxide solution, raising the temperature to 52-57° C. for ball milling, wherein the ball milling time is 1.8-2.2 hours, the ball milling speed is 130-150 rpm, and the ball-to-material ratio is 3-5:1. After the ball milling is completed, the mixture is filtered, washed, and dried, and then the mixture is heated to 356-364° C. at a rate of 3.5-4.5° C. / min, and the mixture is kept warm for 33-37 minutes. Then, the mixture is heated to 435-442° C. at a rate of 1.2-1.8° C. / min, and the mixture is kept warm for 1.8-2 .2h, after the heat preservation treatment is completed, wait for it to naturally return to room temperature, put it into the amino acid mixture, stir it evenly, add hydrochloric acid solution, control the pH value to 6.0-6.4, and perform ultrasonic treatment. The ultrasonic time is 38-42min, the ultrasonic power is 147-153W, and the ultrasonic frequency is 23-28kHz. After the ultrasonic treatment is completed, the temperature is increased to 70-74℃, and the reaction is stirred for 1.8-2.2h. The filtrate is obtained by suction filtration, and the filtrate is concentrated to 22-27% of the original volume, and dried to obtain an amino acid mixture; The particle size of the calcium carbonate is 70-80 nm; The mass ratio of the calcium carbonate, potassium hydroxide solution and amino acid mixture is 11.7-12.4:106-115:112-118; The mass concentration of the potassium hydroxide solution is 22-25%; The amino acid mixture is a mixture of deionized water, L-glutamic acid, L-lysine and L-arginine, and the mass ratio of the deionized water, L-glutamic acid, L-lysine and L-arginine is 200:12-14:8-12:5-8; The mass concentration of the hydrochloric acid solution is 8-12%; (2) Secondary modified bentonite The primary compound fertilizer, potassium sulfate, urea, zinc sulfate and magnesium sulfate are mixed and stirred evenly to obtain a mixture; the mixture is placed in deionized water, primary modified bentonite is added, the temperature is increased to 40-44° C., and homogenization is performed. The homogenization time is 3.5-4.5 minutes and the homogenization pressure is 5.7-6.2 MPa. After the homogenization is completed, the mixture is filtered and dried to obtain secondary modified bentonite; The mass ratio of the primary compound fertilizer, potassium sulfate, urea, zinc sulfate and magnesium sulfate is 22-26:15-18:26-30:0.8-1.2:0.5-0.7; The mass ratio of the mixture, deionized water and primary modified bentonite is 11.0-11.5:145-156:5.0-5.5; (3) Composite Add acrylic acid and sodium hydroxide solution to a reaction container, stir evenly, add secondary modified bentonite, mix evenly, add ammonium persulfate, raise the temperature to 50-54° C., continue to stir evenly, then add N,N-methylenebisacrylamide, perform ultrasonic treatment at 50-54° C., the ultrasonic time is 28-32 minutes, the ultrasonic frequency is 20-24kHz, the ultrasonic power is 84-88W, after the ultrasonic treatment is completed, keep the temperature for reaction for 42-47 minutes, after the reaction is completed, separate and dry to obtain a primary composite; The mass ratio of the acrylic acid, the sodium hydroxide solution, the secondary modified bentonite, the ammonium persulfate and the N,N-methylenebisacrylamide is 16-18:26-30:3.0-3.4:0.44-0.48:0.06-0.10; The mass concentration of the sodium hydroxide solution is 18-22%.
[0011] 3. Secondary compound The guar gum is placed in deionized water, Tween 20 and silane coupling agent kH602 are added, the temperature is raised to 60-64°C, and the mixture is stirred for 2.4-2.7 hours to obtain a mixed solution; the mixed solution is added to the primary composite, carboxymethyl cellulose is added, and the mixture is stirred at 38-42°C for 47-53 minutes. After the stirring is completed, the mixture is dried to obtain a composite fertilizer; The mass ratio of the guar gum, deionized water, Tween 20, and silane coupling agent kH602 is 8.4-8.7:88-93:1.0-1.4:0.8-1.2; The mass ratio of the primary composite, the mixed solution and the carboxymethyl cellulose is 15.3-15.8:34.0-34.3:1.5-1.7.
[0012] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. The present invention prepares composite fertilizer by potassium fluorosilicate slag. First, potassium fluorosilicate slag is activated by ammonia water to generate ammonium fluoride and potassium fluoride. Ammonium fluoride is not easy to be lost when used in composite fertilizer, has long fertilizer effect, contains nitrogen element, can provide nutrition for crop growth, and potassium fluoride can enhance crop absorption and utilization of fertilizer nutrients; then primary composite fertilizer is compounded once, specifically, bentonite is pre-modified, pre-modified liquid can achieve the dispersion of bentonite, expand the interlayer distance of bentonite, and make the surface of bentonite contain amino group and sulfonic acid group, add amino acid mixture to complete the primary modification of bentonite, so that the amino acid mixture is firmly attached to the surface of bentonite, which can provide more calcium element to crops, maintain the stability of cell structure, and the amino acid mixture has good stability, can effectively reduce the loss of calcium element, improve the utilization rate of fertilizer, promote the development of crop root system, enhance the stress resistance of crops, improve the structure and fertility of soil, increase the aggregate structure of soil, and in the compounding step, the mixture is fully adsorbed to bentonite The mixture is loaded in the holes of the mixture, and then combined with the composite step, under the action of the initiator, acrylic acid and sodium hydroxide generate sodium polyacrylate, and under the action of the cross-linking agent, polyacrylic acid and the primary composite are cross-linked and entangled to form a stable three-dimensional network structure, thereby achieving stable coating of the mixture. Sodium polyacrylate has good water retention performance, which can continuously provide more water sources for crops, has strong water holding capacity, helps to promote the growth and development of plants, and achieves good slow-release performance of the primary composite; in the secondary composite step, guar gum is amino-modified by a silane coupling agent, and the amino groups in the mixed solution have good binding force with the amino groups, carboxyl groups and other groups on the surface of the primary composite, and the secondary coating layer is formed on the surface of the primary composite with carboxymethyl cellulose, which is tightly and firmly combined, thereby enhancing the slow-release stability of the compound fertilizer, ensuring the stability of the nutrient release rate, promoting the healthy growth of crops, enhancing the ability to resist diseases and pests and stress, and effectively increasing the yield of crops; 2. The compound fertilizer prepared by the method of the present invention has a water retention rate of 94.8-95.5% after being placed in an environment with a temperature of 26°C and a humidity of 30% for 24.0 hours; 3. The compound fertilizer prepared by the method of the present invention has a nutrient release rate of 10.1-10.6% at 22°C for 10 days, a nutrient release rate of 27.6-28.8% for 30 days, a nutrient release rate of 58.4-60.3% for 45 days, and a nutrient release rate of 85.2-85.9% for 90 days; 3. The compound fertilizer prepared by the method of the present invention is used in the planting of Zhoumai 22. During the growth period of wheat, the incidence of fusarium head blight is 3.5-3.8%, the incidence of leaf blight is 2.8-3.2%, the incidence of aphids is 2.1-2.5%, and the per mu yield of wheat is 550.3-551.4 kg. DETAILED DESCRIPTION
[0013] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.
[0014] Example 1 1. Activation 20g of potassium fluorosilicate was placed in 80g of deionized water, and after being stirred evenly, a 10wt% ammonia solution was added, and the temperature was raised to 50°C for stirring reaction. The reaction time was 30min. After the reaction was completed, the temperature was naturally lowered to room temperature, and the filtrate was obtained by suction filtration. The filtrate was concentrated to 30% of the original volume at 60°C, and dried at 52°C to obtain a primary compound fertilizer; The molar ratio of potassium fluorosilicate to ammonia is 1:8.
[0015] 2. One-time compound (1) Primary modified bentonite 9.5 g of bentonite was placed in 100 g of pre-modified liquid for soaking at a temperature of 50° C. for 35 min. After the soaking, 3.4 g of amino acid mixture was added, and the mixture was stirred for 50 min. The mixture was filtered, washed and dried to obtain a primary modified bentonite. The particle size of the bentonite is 110 nm; The pre-modified liquid is prepared by uniformly mixing 40wt% ethanol solution, kH602, hexadecyltrimethylammonium bromide and sodium lignin sulfonate, wherein the mass ratio of the 40wt% ethanol solution, kH602, hexadecyltrimethylammonium bromide and sodium lignin sulfonate is 120:1.3:1.7:1.0; The preparation method of the amino acid mixture is as follows: 12.0g of calcium carbonate is placed in 110g of 23wt% potassium hydroxide solution, the temperature is raised to 55°C for ball milling, the ball milling time is 2.0h, the ball milling speed is 140rpm, and the ball-to-material ratio is 4:1. After the ball milling is completed, after filtering, washing and drying, the temperature is raised to 360°C at a rate of 4.0°C / min, and the temperature is kept for 35min, and then the temperature is raised to 440°C at a rate of 1.5°C / min, and the temperature is kept for 2.0h. After the temperature is kept, the temperature is naturally restored to room temperature, and then the mixture is added to 115g of amino acid mixture, stirred evenly, and then a 10wt% hydrochloric acid solution is added, the pH value is controlled to 6.2, and ultrasonic treatment is performed, the ultrasonic time is 40min, the ultrasonic power is 150W, and the ultrasonic frequency is 26kHz. After the ultrasonic treatment is completed, the temperature is raised to 72°C, stirred for reaction for 2.0h, and a filtrate is obtained by suction filtration. The filtrate is concentrated to 25% of the original volume and dried to obtain the amino acid mixture. The particle size of the calcium carbonate is 75 nm; The amino acid mixture is a mixture of deionized water, L-glutamic acid, L-lysine and L-arginine, and the mass ratio of the deionized water, L-glutamic acid, L-lysine and L-arginine is 200:13:10:7; (2) Secondary modified bentonite 24g of primary compound fertilizer, 17g of potassium sulfate, 28g of urea, 1.0g of zinc sulfate and 0.6g of magnesium sulfate were mixed and stirred to obtain a mixture; 11.3g of the mixture was placed in 150g of deionized water, 5.2g of primary modified bentonite was added, the temperature was increased to 42°C, and homogenization was performed. The homogenization time was 4.0min and the homogenization pressure was 6.0MPa. After the homogenization was completed, the mixture was filtered and dried to obtain secondary modified bentonite; (3) Composite 17 g of acrylic acid and 28 g of 20 wt% sodium hydroxide solution were added to a reaction container, and after stirring, 3.2 g of secondary modified bentonite was added, and after mixing, 0.46 g of ammonium persulfate was added, the temperature was raised to 52° C., and stirring was continued. Then, 0.08 g of N,N-methylenebisacrylamide was added, and ultrasonic treatment was performed at 52° C. The ultrasonic time was 30 min, the ultrasonic frequency was 22 kHz, and the ultrasonic power was 86 W. After the ultrasonic treatment was completed, the reaction was kept warm for 45 min. After the reaction was completed, it was separated and dried to obtain a primary composite.
[0016] 3. Secondary compound Place 8.5g of guar gum in 90g of deionized water, add 1.2g of Tween 20 and 1.0g of silane coupling agent kH602, raise the temperature to 62°C, keep stirring for 2.5h to obtain a mixed solution; add 34.1g of the mixed solution to 15.5g of the primary composite, add 1.6g of carboxymethyl cellulose, stir at 40°C for 50min, and after the stirring is completed, dry to obtain a compound fertilizer.
[0017] Example 2 1. Activation 10g of potassium fluorosilicate was placed in 90g of deionized water, and after being stirred evenly, a 15wt% ammonia solution was added, and the temperature was raised to 60°C for stirring reaction. The reaction time was 90min. After the reaction was completed, the temperature was naturally lowered to room temperature, and the filtrate was obtained by suction filtration. The filtrate was concentrated to 28% of the original volume at 58°C, and dried at 50°C to obtain a primary compound fertilizer; The molar ratio of potassium fluorosilicate to ammonia is 1:10.
[0018] 2. One-time compound (1) Primary modified bentonite 9.3 g of bentonite was placed in 95 g of pre-modified liquid for soaking at 48° C. for 32 min. After the soaking, 3.2 g of amino acid mixture was added, and stirring was continued for 48 min. The mixture was filtered, washed and dried to obtain a primary modified bentonite. The particle size of the bentonite is 100 nm; The pre-modified liquid is prepared by uniformly mixing 37wt% ethanol solution, kH602, hexadecyltrimethylammonium bromide and sodium lignin sulfonate, wherein the mass ratio of the 37wt% ethanol solution, kH602, hexadecyltrimethylammonium bromide and sodium lignin sulfonate is 120:1.1:1.5:0.8; The preparation method of the amino acid mixture is as follows: 11.7g of calcium carbonate is placed in 106g of 22wt% potassium hydroxide solution, the temperature is raised to 52°C for ball milling, the ball milling time is 1.8h, the ball milling speed is 130rpm, and the ball-to-material ratio is 3:1. After the ball milling is completed, after filtering, washing and drying, the temperature is raised to 356°C at a rate of 3.5°C / min, and the temperature is kept for 37min, and then the temperature is raised to 435°C at a rate of 1.2°C / min, and the temperature is kept for 1.8h. After the temperature is kept, the temperature is naturally restored to room temperature, and then the mixture is added to 112g of amino acid mixed solution, stirred evenly, and then 8wt% hydrochloric acid solution is added, the pH value is controlled to 6.0, and ultrasonic treatment is performed, the ultrasonic time is 38min, the ultrasonic power is 147W, and the ultrasonic frequency is 23kHz. After the ultrasonic treatment is completed, the temperature is raised to 70°C, the reaction is stirred for 1.8h, and a filtrate is obtained by suction filtration. The filtrate is concentrated to 22% of the original volume and dried to obtain an amino acid mixture. The particle size of the calcium carbonate is 70 nm; The amino acid mixture is a mixture of deionized water, L-glutamic acid, L-lysine and L-arginine, and the mass ratio of the deionized water, L-glutamic acid, L-lysine and L-arginine is 200:12:8:5; (2) Secondary modified bentonite 22g of primary compound fertilizer, 15g of potassium sulfate, 26g of urea, 0.8g of zinc sulfate and 0.5g of magnesium sulfate were mixed and stirred to obtain a mixture; 11.0g of the mixture was placed in 145g of deionized water, 5.0g of primary modified bentonite was added, the temperature was increased to 40°C, and homogenization was performed. The homogenization time was 3.5min and the homogenization pressure was 6.2MPa. After the homogenization was completed, the mixture was filtered and dried to obtain secondary modified bentonite; (3) Composite 16 g of acrylic acid and 26 g of 18 wt % sodium hydroxide solution were added to a reaction container, and after stirring, 3.0 g of secondary modified bentonite was added, and after mixing, 0.44 g of ammonium persulfate was added, the temperature was raised to 50° C., and stirring was continued. Then, 0.06 g of N, N-methylenebisacrylamide was added, and ultrasonic treatment was performed at 50° C. The ultrasonic time was 28 min, the ultrasonic frequency was 20 kHz, and the ultrasonic power was 84 W. After the ultrasonic treatment was completed, the reaction was kept warm for 42 min. After the reaction was completed, it was separated and dried to obtain a primary composite.
[0019] 3. Secondary compound Place 8.4 g of guar gum in 88 g of deionized water, add 1.0 g of Tween 20 and 0.8 g of silane coupling agent kH602, raise the temperature to 60°C, keep stirring for 2.7 hours to obtain a mixed solution; add 34.0 g of the mixed solution to 15.3 g of the primary composite, add 1.5 g of carboxymethyl cellulose, stir at 38°C for 47 minutes, and after stirring, dry to obtain a compound fertilizer.
[0020] Example 3 1. Activation 50g of potassium fluorosilicate was placed in 50g of deionized water, and after being stirred evenly, a 25wt% ammonia solution was added, and the temperature was raised to 90°C for stirring reaction. The reaction time was 120min. After the reaction was completed, the temperature was naturally lowered to room temperature, and the filtrate was obtained by suction filtration. The filtrate was concentrated to 33% of the original volume at 62°C, and dried at 54°C to obtain a primary compound fertilizer; The molar ratio of potassium fluorosilicate to ammonia is 1:5.
[0021] 2. One-time compound (1) Primary modified bentonite 9.8 g of bentonite was placed in 110 g of pre-modified liquid for soaking at a temperature of 52° C. for 38 min. After the soaking, 3.7 g of amino acid mixture was added, and stirring was continued for 52 min. The mixture was filtered, washed, and dried to obtain a primary modified bentonite. The particle size of the bentonite is 120 nm; The pre-modified liquid is prepared by uniformly mixing 42wt% ethanol solution, kH602, hexadecyltrimethylammonium bromide and sodium lignin sulfonate, wherein the mass ratio of the 42wt% ethanol solution, kH602, hexadecyltrimethylammonium bromide and sodium lignin sulfonate is 120:1.5:2.0:1.2; The preparation method of the amino acid mixture is as follows: 12.4g of calcium carbonate is placed in 115g of 25wt% potassium hydroxide solution, the temperature is raised to 57°C for ball milling, the ball milling time is 2.2h, the ball milling speed is 150rpm, and the ball-to-material ratio is 5:1. After the ball milling is completed, after filtering, washing and drying, the temperature is raised to 364°C at a rate of 4.5°C / min, and the temperature is kept for 33min, and then the temperature is raised to 442°C at a rate of 1.8°C / min, and the temperature is kept for 2.2h. After the temperature is kept, the temperature is naturally restored to room temperature, and then the mixture is added to 118g of amino acid mixture, stirred evenly, and then a 12wt% hydrochloric acid solution is added, the pH value is controlled to 6.4, and ultrasonic treatment is performed, the ultrasonic time is 42min, the ultrasonic power is 153W, and the ultrasonic frequency is 28kHz. After the ultrasonic treatment is completed, the temperature is raised to 74°C, and the reaction is stirred for 2.2h. A filtrate is obtained by suction filtration, and the filtrate is concentrated to 27% of the original volume, and dried to obtain an amino acid mixture; The particle size of the calcium carbonate is 80 nm; The amino acid mixture is a mixture of deionized water, L-glutamic acid, L-lysine and L-arginine, and the mass ratio of the deionized water, L-glutamic acid, L-lysine and L-arginine is 200:14:12:8; (2) Secondary modified bentonite 26g of primary compound fertilizer, 18g of potassium sulfate, 30g of urea, 1.2g of zinc sulfate and 0.7g of magnesium sulfate were mixed and stirred to obtain a mixture; 11.5g of the mixture was placed in 156g of deionized water, 5.5g of primary modified bentonite was added, the temperature was increased to 44°C, and homogenization was performed. The homogenization time was 4.5min and the homogenization pressure was 5.7MPa. After the homogenization was completed, the mixture was filtered and dried to obtain secondary modified bentonite; (3) Composite 18 g of acrylic acid and 30 g of 22 wt% sodium hydroxide solution were added to a reaction container, and after stirring, 3.4 g of secondary modified bentonite was added, and after mixing, 0.48 g of ammonium persulfate was added, the temperature was raised to 54° C., and stirring was continued. Then, 0.10 g of N,N-methylenebisacrylamide was added, and ultrasonic treatment was performed at 54° C. The ultrasonic time was 32 min, the ultrasonic frequency was 24 kHz, and the ultrasonic power was 88 W. After the ultrasonic treatment was completed, the reaction was kept warm for 47 min. After the reaction was completed, it was separated and dried to obtain a primary composite.
[0022] 3. Secondary compound Place 8.7g of guar gum in 93g of deionized water, add 1.4g of Tween 20 and 1.2g of silane coupling agent kH602, raise the temperature to 64°C, keep stirring for 2.4h to obtain a mixed solution; add 34.3g of the mixed solution to 15.8g of the primary composite, add 1.7g of carboxymethyl cellulose, stir at 428°C for 53min, and after stirring, dry to obtain a compound fertilizer.
[0023] Comparative Example 1 Based on Example 1, the changes are as follows: (1) The activation step is omitted and the primary compound fertilizer is replaced with potassium fluorosilicate in the secondary modified bentonite step of the primary compounding process; (2) The secondary compounding step is omitted, and the primary compound obtained is the compound fertilizer; The rest of the operations are the same.
[0024] Comparative Example 2 Based on Example 1, the change is that in one compounding process, (1) The first modified bentonite step is omitted; in the second modified bentonite step, the first modified bentonite is replaced by an equal amount of untreated bentonite, wherein the particle size of the bentonite is 110 nm; (2) Omitting the compounding step; in the secondary compounding step, replacing the primary compound with secondary modified bentonite in equal amounts; The rest of the operations are the same.
[0025] Performance Testing The composite fertilizers prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to the following performance tests, as follows: 1. Water retention performance The compound fertilizers prepared in Example 1-3 and Comparative Example 1-2 were dried at 80°C for 2.0h. After drying, they were placed in 8 times the mass of deionized water and soaked at room temperature for 48.0h. After soaking, the surface moisture was wiped off until no water droplets fell on the surface. The weight was recorded as m1. Then, they were placed in an environment with a temperature of 26°C and a humidity of 30% and allowed to stand for 24.0h. The weight was recorded as m2 again. The water retention rate of each compound fertilizer was calculated. Water retention rate = (m1-m2) / m1×100%; According to the above method, the water retention rate of the compound fertilizers prepared in Examples 1-3 and Comparative Examples 1-2 was measured as follows:
[0026] 2. Sustained release performance According to the method in GB / T23348-2009 "Slow-release Fertilizer", the nutrient release performance of the compound fertilizers prepared in Examples 1-3 and Comparative Examples 1-2 was measured at 22°C at different times. The test results are as follows:
[0027] 3. Resistance to diseases and pests A 20-mu experimental base was selected in Shouguang City, Shandong Province, and the compound fertilizers prepared in Examples 1-3 and Comparative Examples 1-2 were used in a wheat planting test, and the wheat variety was Zhoumai 22; specifically, the experimental base was evenly divided into 5 mutually isolated test areas, and then the compound fertilizers in Examples 1-3 and Comparative Examples 1-2 were used to carry out wheat planting tests respectively; during the planting process, the wheat was managed by conventional planting methods, wherein the amount of compound fertilizer, the timing of application, the number of plantings, and the water content were all controlled in the same manner, the incidence of wheat diseases and insect pests during the growth cycle of wheat was counted, and the per-mu yield of wheat was counted after the wheat matured, as follows:
[0028] The invention prepares compound fertilizer by potassium fluorosilicate slag. First, the potassium fluorosilicate slag is activated by ammonia water to generate ammonium fluoride and potassium fluoride. The ammonium fluoride is not easy to be lost when used in the compound fertilizer, has a long fertilizer effect, contains nitrogen elements, can provide nutrition for crop growth, and potassium fluoride can enhance the crop's absorption and utilization of fertilizer nutrients. Then, the primary compound fertilizer is compounded once, specifically, bentonite is pre-modified, the pre-modified liquid can achieve the dispersion of bentonite, expand the interlayer spacing of bentonite, and make the bentonite surface contain amino groups and sulfonic acid groups, and an amino acid mixture is added to complete the primary modification of bentonite, so that the amino acid mixture is firmly attached to the bentonite surface, which can provide more calcium elements to the crop and maintain the stability of the cell structure. The amino acid mixture has good stability, can effectively reduce the loss of calcium elements, improve the utilization rate of fertilizer, promote the development of crop root system, enhance the stress resistance of crops, improve the structure and fertility of soil, and increase the aggregate structure of soil. In the compounding step, the mixture is fully adsorbed to the bentonite. The mixture is loaded in the holes, and then combined with the compounding step, under the action of the initiator, acrylic acid and sodium hydroxide generate sodium polyacrylate, and under the action of the cross-linking agent, polyacrylic acid and the primary compound are cross-linked and entangled with each other to form a stable three-dimensional network structure, thereby achieving stable coating of the mixture. Sodium polyacrylate has good water retention performance, which can continuously provide more water sources for crops, has strong water holding capacity, helps to promote the growth and development of plants, and achieves good slow-release performance of the primary compound; in the secondary compounding step, guar gum is amino-modified by a silane coupling agent, and the amino groups in the mixed solution have good binding force with the amino groups, carboxyl groups and other groups on the surface of the primary compound, and the secondary coating layer is formed on the surface of the primary compound in combination with carboxymethyl cellulose, which is tightly and firmly combined, thereby enhancing the slow-release stability of the compound fertilizer, ensuring the stability of the nutrient release rate, promoting the healthy growth of crops, enhancing the ability to resist diseases and pests and stress, and effectively increasing the yield of crops.
[0029] In Comparative Example 1, the activation step is omitted, and potassium fluorosilicate is directly used in compound fertilizer. The fertilizer efficiency of potassium fluorosilicate is poor and cannot meet the needs of crop growth. The secondary compounding step is also omitted, and the primary compound is directly used as compound fertilizer. In Comparative Example 1, the secondary coating layer is omitted, which weakens the slow-release performance of the compound fertilizer, makes the slow-release rate unstable, reduces the disease and pest resistance of the crop, and ultimately reduces the crop yield.
[0030] Comparative Example 2 omits the step of modifying bentonite once, and directly mixes potassium fluorosilicate with bentonite. The bentonite has strong aggregation and poor adsorption for compound fertilizer. The amino acid mixture component is omitted, which reduces the stress resistance of crops, and the structure and fertility of the soil are poor. The compounding step is also omitted, and the cross-linking of sodium polyacrylate and secondary modified bentonite cannot be achieved, thereby failing to form a stable cross-linked network structure, weakening the water absorption and water holding capacity of the compound fertilizer, thereby making the slow release rate of the compound fertilizer unstable and the slow release performance poor, ultimately reducing crop yields.
[0031] Unless otherwise specified, all ratios and percentages described in the present invention are by mass ratios and percentages are by mass percentages.
[0032] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing compound fertilizer by activating potassium fluorosilicate slag, characterized in that: It includes activation, primary compounding and secondary compounding steps; The activation step is to place potassium fluorosilicate in deionized water, add ammonia solution, and react at 60-90° C. for 90-120 minutes to obtain primary compound fertilizer; The first compounding step includes first modified bentonite, second modified bentonite and compounding step; The step of primary modified bentonite is to place the bentonite in a pre-modified liquid for immersion, and then add the amino acid mixture to obtain the primary modified bentonite; The pre-modified liquid is prepared by mixing ethanol solution, KH602, hexadecyltrimethylammonium bromide and sodium lignin sulfonate; The compounding step comprises adding acrylic acid and sodium hydroxide solution into a reaction container, adding secondary modified bentonite and mixing evenly, adding ammonium persulfate, stirring evenly at 50-54° C., adding N,N-methylenebisacrylamide for ultrasonic treatment, and keeping the temperature for reaction for 42-47 minutes to obtain a primary compound; The secondary compounding step comprises placing guar gum in deionized water, adding Tween 20 and silane coupling agent kH602, stirring and reacting at 60-64° C. to obtain a mixed solution; and adding the mixed solution and carboxymethyl cellulose to the primary compound to obtain a compound fertilizer.
2. The method for preparing composite fertilizer by activating potassium fluorosilicate slag according to claim 1, characterized in that: In the activation step, the mass ratio of potassium fluorosilicate to deionized water is 10-50:50-90; The mass concentration of the ammonia solution is 15-25%; The molar ratio of potassium fluorosilicate to ammonia is 1:5-10.
3. The method for preparing composite fertilizer by activating potassium fluorosilicate slag according to claim 1, characterized in that: In the step of once modifying bentonite, the soaking temperature is 48-52° C. and the soaking time is 32-38 min; The particle size of the bentonite is 100-120nm; The mass ratio of the bentonite, the pre-modified liquid and the amino acid mixture is 9.3-9.8:95-110:3.2-3.
7.
4. The method for preparing composite fertilizer by activating potassium fluorosilicate slag according to claim 1, characterized in that: In the step of modifying bentonite once, the mass concentration of the ethanol solution in the pre-modified liquid is 37-42%; The mass ratio of the ethanol solution, KH602, hexadecyltrimethylammonium bromide and sodium lignin sulfonate is 120:1.1-1.5:1.5-2.0:0.8-1.
2.
5. The method for preparing composite fertilizer by activating potassium fluorosilicate slag according to claim 1, characterized in that: In the step of modifying bentonite once, the preparation method of the amino acid mixture is as follows: placing calcium carbonate in a potassium hydroxide solution, raising the temperature to 52-57°C for ball milling, filtering, washing and drying after the ball milling, raising the temperature to 356-364°C at a rate of 3.5-4.5°C / min, keeping the temperature for 33-37min, and then raising the temperature to 435-442°C at a rate of 1.2-1.8°C / min, keeping the temperature for 1.8-2.2h, after the insulation treatment, wait for it to naturally return to room temperature, put it into the amino acid mixture, stir evenly, add hydrochloric acid solution, control the pH value to 6.0-6.4, and perform ultrasonic treatment, after the ultrasonic treatment, raise the temperature to 70-74°C, stir and react for 1.8-2.2h, obtain a filtrate by suction filtration, concentrate the filtrate to 22-27% of the original volume, and obtain an amino acid mixture by drying; The particle size of the calcium carbonate is 70-80 nm; The mass ratio of the calcium carbonate, potassium hydroxide solution and amino acid mixture is 11.7-12.4:106-115:112-118; The mass concentration of the potassium hydroxide solution is 22-25%; The amino acid mixture is a mixture of deionized water, L-glutamic acid, L-lysine and L-arginine, and the mass ratio of the deionized water, L-glutamic acid, L-lysine and L-arginine is 200:12-14:8-12:5-8; The mass concentration of the hydrochloric acid solution is 8-12%.
6. The method for preparing compound fertilizer by activating potassium fluorosilicate slag according to claim 1, characterized in that: The secondary modified bentonite step comprises: mixing primary compound fertilizer, potassium sulfate, urea, zinc sulfate and magnesium sulfate, stirring evenly to obtain a mixture; placing the mixture in deionized water, adding primary modified bentonite, raising the temperature to 40-44° C., performing homogenization treatment, the homogenization time is 3.5-4.5 min, the homogenization pressure is 5.7-6.2 MPa, and after the homogenization treatment is completed, filtering and drying to obtain the secondary modified bentonite; The mass ratio of the primary compound fertilizer, potassium sulfate, urea, zinc sulfate and magnesium sulfate is 22-26:15-18:26-30:0.8-1.2:0.5-0.7; The mass ratio of the mixture, deionized water and primary modified bentonite is 11.0-11.5:145-156:5.0-5.
5.
7. The method for preparing compound fertilizer by activating potassium fluorosilicate slag according to claim 1, characterized in that: In the compounding step, the ultrasonic treatment has an ultrasonic time of 28-32 min, an ultrasonic frequency of 20-24 kHz, and an ultrasonic power of 84-88 W.
8. The method for preparing compound fertilizer by activating potassium fluorosilicate slag according to claim 1, characterized in that: The mass ratio of the acrylic acid, the sodium hydroxide solution, the secondary modified bentonite, the ammonium persulfate and the N,N-methylenebisacrylamide is 16-18:26-30:3.0-3.4:0.44-0.48:0.06-0.10; The mass concentration of the sodium hydroxide solution is 18-22%.
9. The method for preparing compound fertilizer by activating potassium fluorosilicate slag according to claim 1, characterized in that: In the secondary compounding step, the mass ratio of the guar gum, deionized water, Tween 20, and silane coupling agent kH602 is 8.4-8.7:88-93:1.0-1.4:0.8-1.2; The mass ratio of the primary composite, the mixed solution and the carboxymethyl cellulose is 15.3-15.8:34.0-34.3:1.5-1.7.
Citation Information
Patent Citations
Method for preparing fluoride salt from phosphorus ore associated fluorine
CN114031100A
Method for preparing high-activity potassium fluoride by using fluorine-containing slag
CN118164501A
Bean vegetable seed coating agent and preparation method thereof
CN118515517A
Preparation method of hydrolyzed amino acid suspended fertilizer
CN118530077A
Fertilizer synergist, preparation method and application thereof
CN118561641A